SCREENING OF DOGS FOR LEPTOSPIROSIS IN CAUVERY DELTA REGION OF TAMIL NADU - Khedekar Prajyot Hemant; S. Balakrishnan; B. Puvarajan; A. Sangeetha; K. Manimaran; T.M.A. Senthilkumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Leptospirosis is a zoonotic disease caused by pathogenic species of Leptospira interrogans. Dogs can act as maintenance host for some serovars and transmit to other animals and humans through direct and/or indirect contact with urine or contaminated water and soil. A study was conducted to identify the presence of Leptospira and assessment of seroprevalence in apparently healthy dogs in Cauvery delta region (Thanjavur, Thiruvarur and Nagapattinam districts) of Tamil Nadu. Serum (n=50) and urine (n=50) samples were collected randomly from 50 dogs with history of non vaccination to leptospirosis. Dark field microscopic (DFM) examination revealed the presence of Leptospira in 12.0 per cent of serum and 24.0 per cent of urine samples. Serological screening was done by microscopic agglutination test (MAT) using a battery of 12 Leptospira serovars (representing the serogroups of Australis, Autumnalis, Ballum, Canicola, Grippotyphosa, Hardjo, Hebdomadis, Icterohaemorrhagiae, Javanica, Pomona, Pyrogenes and Tarassovi), which revealed 56.0 per cent seropositivity to either one or several serovars, which was Icterohaemorrhagiae (46.4 per cent), Grippotyphosa (32.1 per cent), Australis (32.1 per cent), Canicola (25.0 per cent) and Autumnalis (17.9 per cent) with highly significant difference (p